2020
DOI: 10.3390/pathogens9100825
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipoteichoic Acid Attenuates Toll-Like Receptor Dependent Dendritic Cells Activation and Inflammatory Response

Abstract: Toll-like receptor (TLR) signaling is an indispensable factor in immune cells activation. Many TLR ligands have been identified, and were characterized the immunological functions such as inflammatory cytokine production in immune cells. However, the anti-inflammatory response in TLR ligand-mediated manner is poorly understood. In this report, we show that bacterial lipoteichoic acid (LTA), which is a TLR2 ligand from gram-positive bacteria including Staphylococcus aureus (S. aureus), suppresses TLR-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Liver and kidney mononuclear cells (MNCs) were prepared by following a method described in a previous report ( 19 ). Briefly, the organs were finely minced in a dish in cell culture medium, and then further crushed on a 70 μM cell strainer.…”
Section: Methodsmentioning
confidence: 99%
“…Liver and kidney mononuclear cells (MNCs) were prepared by following a method described in a previous report ( 19 ). Briefly, the organs were finely minced in a dish in cell culture medium, and then further crushed on a 70 μM cell strainer.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the crucial mechanism involved in PD-L1 upregulation in neutrophils during MRSA infection. For this purpose, we prepared HK-SA and isolated structural components, such as cell wall extracts (CWE), cell protein extracts (CPE), lipoproteins (LP), and nucleic acids (DNA, RNA), from MRSA culture following the represented procedures based on previous publications (Figure 3A) [13][14][15]. In vitro HK-SA stimulation showed that PD-L1 expressions were significantly increased in neutrophils treated with HK-SA at concentrations greater than 5.0x10 7 CFU/mL (MOI=1:5), and the expressions were dose dependently increased resulted in the largest PD-L1+ cells in the culture stimulated with 5.0x10 8 CFU/mL (MOI=1:50) of HK-SA (Figure 3A).…”
Section: Mrsa Recognition Via Tlrs Increases Pd-l1 Expression In Neut...mentioning
confidence: 99%
“…Previous publications have described the crucial roles of TLRs in S. aureus recognition [13][14][15][16][17][18]. Therefore, we decided to investigate whether TLRs and their downstream factor, myeloid differentiation factor 88 (Myd88), contribute to PD-L1 upregulation in neutrophils.…”
Section: Mrsa Recognition Via Tlrs Increases Pd-l1 Expression In Neut...mentioning
confidence: 99%
“…Biofilms, as a physical barrier, hinder the contact between antigen-presenting cells (APCs) and pathogens, while also modifying pathogen antigenicity or concealing crucial immunogenic epitopes, making it challenging for APCs to continuously and effectively recognize pathogen-specific antigens. Simultaneously, the immune-suppressive environment induced by biofilms generates immunoregulatory molecules that interfere with the activity of APCs and disturb their maturation, antigen capture, processing, and presentation abilities, thereby inhibiting T-cell activation. Furthermore, biofilms can stimulate the emergence of regulatory T cells (T reg s), a distinct type of T cells that plays a critical role in immune suppression and tolerance. Biofilms disrupt the formation and function of adaptive immune responses through the above mechanisms, enabling bacterial persistence and leading to chronic and recurrent infections. Therefore, designing an immunomodulatory strategy that destroys the biofilm barrier, reverses the biofilm-induced immunosuppressive microenvironment, and activates adaptive immune responses could effectively combat biofilm infections.…”
Section: Introductionmentioning
confidence: 99%